Application of phage surface display for the identification of Eu3+-binding peptides - Techert, Gerda; Drobot, Björn; Braun, Robert; Bloss, Christoph; Schönberger, Nora; Matys, Sabine; Pollmann, Katrin; Lederer, Franziska L. (Frontiers in Bioengineering and Biotechnology, 2025)
Europium as one of the rare earth elements (REE) has outstanding properties in terms of its application for high-tech and renewable energy products. The high supply risk of REE, coupled with their low recovery rates from secondary sources, necessitates innovative recycling approaches. We introduce a phage display-based peptide biosorbent recycling technology that offers a cost-effective and environmentally friendly solution for recovering metal ions, supporting circular economy goals. In this study, we used phage surface display to screen for peptides with high affinity for europium (III) ions (Eu3+). Performing several independent biopanning experiments with the Ph.D.-12 Phage Display Peptide Library and different elution methods as well as combining them with next-generation sequencing, we identified eight peptides with moderate to good affinities for Eu3+ ions, verified by time-resolved laser fluorescence spectroscopy. The peptides EALTVNIKREME as well as DVHHVDGNDLQPFEGGGS and DSIHSDVTKDGRYPVEGGGS, the latter are variants of enriched dodecamers, proved to be the best candidates for future biosorption and selectivity studies. This study underscores the potential of phage surface display for peptide-based REE recovery, laying the foundation for selective recycling technologies from secondary raw materials.